Heterotopic ossification after total ankle replacement: The role of prosthesis alignment. Issue 2 (June 2017) - Manegold, Sebastian; Springer, Alexander; Landvoigt, Kristin; Tsitsilonis, Serafim
Highlights: Formation of heterotopic ossifications after TAR grows over time (up to 100% after 3 years). Formation of heterotopic ossifications does not seem to be associated with TAR alignment. Heterotopic ossifications could be attributed to prosthesis design. Abstract: Background: The aetiology of heterotopic ossifications (HO) after total ankle arthroplasty (TAR) remains controversial. The aim of the study was to evaluate the prevalence and localisation of HO and the effect of alignment. Methods: 88 TARs with a series of radiological controls and follow-up of 36 months were evaluated. Frontal and sagittal alignment parameters (alfa and beta angle defined by Hintermann) and tibial coverage were evaluated. Results: The prevalence and grading of HO increased over time, mostly in the posterior gutter. Varus alignment correlated with HO increase in the ventral and lateral gutters the first year. A dorsally located rotational centre correlated with total HO growth and HO in the posterior gutter. These correlations were not detected after 3 years, as HO were seen in all prostheses, regardless of alignment. Conclusions: HO grow over time with a prevalence up to 100% after 3 years. TAR alignment correlates with gutter-specific HO formation within the first year.